Cuidados de enfermería en el post operatorio a pacientes de craneotomía - Caiza Lema, Jonathan Jairo (2024)
Introduction: this article exposes the importance of the application of post-operative nursing care to patients with craniotomies, which contributes to their recovery, reducing the mortality and morbidity associated with this type of intervention. Objective: to describe post-operative nursing care for craniotomy patients through a bibliographic review. Materials and methods: this article has a qualitative approach, with a non experimental research design with analytical-synthetic methods and induction-deduction, in addition to using the PRISMA method: An exhaustive search was carried out in different databases and reliable sources, obtaining 80 bibliographic sources that were subjected to processes such as PICO question, health descriptors, inclusion criteria to approve 15 articles. Results: It is evident that nursing care in post-operative patients of craniotomies is essential to prevent and avoid future complications during the recovery and stay of the patient, in addition this care must be provided by highly trained professionals in the area, in this way the reduction of the mortality and morbidity of patients in this type of intervention is guaranteed. Conclusion: During the investigation it was possible to identify the effectiveness of nursing care in post-craniotomy patients in processes such as: haemodynamic stability, monitoring of vital signs and intracranial pressure, drainage control, evaluation of pain and emotional support to the patient.